Harnessing the power of distributed energy resources in developing countries: What can be learned from the experiences of global leaders? - Gabriela Elizondo; Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2023)
The role of distributed energy resources (DERs) in future power systems is becoming increasingly important due to the ongoing transformation of the electricity sector towards carbon neutrality and higher decentralization. As changes in the demand side continue, such as the adoption of electric vehicles (EVs) and heat pumps, and the connection of DERs to the grid by prosumers and aggregators, coordination between supply- and demand-side resources becomes more critical. Both developed and developing countries have a strong incentive to deploy DERs. In developed countries, there is a growing demand for cleaner and more sustainable energy sources, as well as a desire to reduce dependence on centralized power grids. As renewable energy sources like solar and wind power continue to gain a larger share of the energy supply, there is a growing need for an optimized and flexible power system that can effectively manage the variability of these sources. In developing countries, the deployment of DERs has the potential not only to reduce greenhouse gas emissions but also to improve energy access, promote energy security, and mitigate the risks associated with importing fossil fuels. This is why these economies have started to deploy growing DER volumes, particularly distributed solar, battery energy storage, and EV charging load. Central to this paper is our exploration into the dynamics, opportunities, and challenges of implementing DERs in various energy contexts, particularly underscoring the disparities and commonalities between developed and developing regions. The principal research objective is to unearth the strategic, regulatory, and technological underpinnings that have facilitated the proliferation of DERs in pioneering regions such as Australia, the UK, Germany, and California, and subsequently, to extract actionable insights and tailored recommendations for accelerating the integration of DERs in developing countries. By analyzing the distinct pathways, policy landscapes, and outcomes realized by these frontrunner regions, we aim to distill lessons and strategies that can pragmatically be adapted and applied to the nuanced energy ecosystems prevalent in developing countries. These recommendations cover a range of areas, including end-user tariffs, network access pricing, addressing fixed system costs in the presence of decentralized resources, DER aggregation, enabling DER participation in multiple markets to maximize revenue, reforming electricity distribution utilities, and establishing coordination mechanisms between transmission and distribution system operators (DSOs). The lessons learned can inform developing countries' efforts to integrate DERs and transition to a more sustainable energy future.
Keywords: 330; aggregation; Developing Countries; Distributed energy resources (DERs); international experiences; regulatory instruments; Renewable Energy; retail electricity tariffs; TSO-DSO coordination; wholesale electricity market design